Exhaust gas purification catalyst

The exhaust gas purification catalyst, utilizing zeolites with Cu and additional metals like Mn or La, addresses the challenge of stricter NOx regulations and N2O emissions by optimizing pore volume ratios, resulting in enhanced NOx purification and reduced N2O production.

JP2025058889APending Publication Date: 2025-04-09TOKYO ROKI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024104323
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-27
Filing Date
2024-06-27
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Current SCR catalysts face challenges in meeting stricter NOx emission regulations while minimizing the production of N2O, a potent greenhouse gas, due to increased Cu loading which enhances NOx reduction but also increases O production.

Method used

The development of an exhaust gas purification catalyst featuring a zeolite substrate with Cu and a metal other than Cu, such as Mn or La, where the pore volume ratio of zeolites with metals to those without is optimized between 0.85 and 0.99, effectively reducing NOx and N2O emissions.

Benefits of technology

This catalyst achieves improved NOx purification performance while significantly suppressing N2O emissions, adhering to stricter emission regulations and reducing greenhouse gas production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058889000001_ABST
    Figure 2025058889000001_ABST
Patent Text Reader

Abstract

To provide an exhaust gas purification catalyst capable of satisfying both NOx purification and inhibition of N2O discharge.SOLUTION: An exhaust gas purification catalyst includes a base material and a catalyst carried on a surface of the base material. The catalyst contains zeolite including therein Cu and metal other than Cu.SELECTED DRAWING: Figure 1A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst for purifying exhaust gas. [Background technology]

[0002] Vehicles equipped with diesel engines that use diesel fuel emit carbon monoxide (CO), nitrogen oxides (NOx), and unburned hydrocarbons (HC) that are produced when diesel fuel is burned. CO, NOx, and HC are harmful gases, so emissions are regulated, and vehicles equipped with diesel engines are equipped with several types of catalysts to remove these harmful gases.

[0003] One such catalyst is the selective catalytic reduction catalyst (SCR) catalyst. SCR catalysts use reducing agents such as urea to selectively reduce NOx to N2 and H2O, rendering them harmless.

[0004] The mainstream SCR catalyst is a catalyst in which copper (Cu), an active species, is supported on chabazite (CHA)-type zeolite, a type of zeolite (see, for example, Patent Document 1). One method for improving the NOx reduction (hereinafter also referred to as NOx purification) performance of a catalyst is to increase the amount of Cu supported in the zeolite. However, increasing the amount of Cu supported increases the amount of N2O, a by-product, generated at the same time as the NOx reduction reaction. N2O is a gas that has a greenhouse effect approximately 300 times that of CO2, and has been subject to recent exhaust regulations. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2023-079713 A Summary of the Invention [Problem to be solved by the invention]

[0006] Regarding N2O, emission regulations are expected to become even stricter in the future. In order to comply with the new emission regulations, it is necessary to improve the NOx purification performance of SCR catalysts while at the same time suppressing the production of N2O, a by-product.

[0007] An object of the present invention is to provide an exhaust gas purification catalyst that can simultaneously purify NOx and suppress N2O emissions. [Means for solving the problem]

[0008] The exhaust gas purifying catalyst of the present invention is A catalyst for purifying exhaust gas, comprising a substrate and a catalyst supported on a surface of the substrate, The catalyst is characterized in that it contains zeolite containing Cu and the metal other than Cu.

[0009] In another aspect of the present invention, In zeolites, the ratio of the pore volume of a zeolite containing Cu and metals other than Cu to the pore volume of a zeolite not containing metals other than Cu (pore volume of a zeolite containing metals other than Cu (cm 3 / g) / pore volume of zeolite containing no metals other than Cu (cm 3 / g)) is preferably 0.85 to 0.99.

[0010] In another aspect of the present invention, In zeolite, the ratio of the pore volume of a zeolite containing Cu and a metal other than Cu to the pore volume of a zeolite not containing the metal other than Cu (pore volume of a zeolite containing a metal other than Cu (cm 3 / g) / pore volume of zeolite containing no metals other than Cu (cm 3 / g)) is preferably 0.87 to 0.99.

[0011] In another aspect of the present invention, The metal other than Cu is preferably at least one selected from manganese (Mn), iron (Fe), zinc (Zn), lanthanum (La), neodymium (Nd), boron (B), and cerium (Ce).

[0012] In another aspect of the present invention, The metal other than Cu is preferably at least one selected from La and Mn.

[0013] In another aspect of the present invention, The ratio of aluminum (Al) to metals other than Cu in the zeolite in the catalyst (metals other than Cu / Al) is preferably 0.01 to 0.33. Effect of the Invention

[0014] According to the present invention, it is possible to provide an exhaust gas purification catalyst that can achieve both NOx purification and suppression of N2O emissions. [Brief description of the drawings]

[0015] [Figure 1A] FIG. 1A shows the results of observing metal atoms in the zeolite in Example 9. [Figure 1B] FIG. 1B shows the observation results of metal atoms in the zeolite in Example 9 after image processing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] (Exhaust gas purification catalyst) The exhaust gas purifying catalyst according to the embodiment includes a substrate and a catalyst supported on the surface of the substrate, and further includes other members as required.

[0017] <Base material> The substrate is not particularly limited as long as it is one that is used in ordinary exhaust gas purification catalysts and can be appropriately selected depending on the purpose. Examples of the substrate include a honeycomb structure and a wall-flow structure. The substrate is not particularly limited as long as it is one that is used in ordinary exhaust gas purification catalysts and can be appropriately selected depending on the purpose. Examples of the substrate include cordierite, SiC, and alumina titanate. The size of the substrate is not particularly limited and can be appropriately selected depending on the purpose.

[0018] <Catalyst> The catalyst is supported on the surface of the substrate and promotes the reduction reaction of NOx. The catalyst contains a zeolite and, if necessary, further contains other components.

[0019] <<Zeolite>> Zeolite is a compound that has a TO4 unit (T element is an element other than oxygen that constitutes the framework) as a basic unit, which is composed of silicon (Si) or Al and oxygen. Specific examples include crystalline porous aluminosilicate, crystalline porous aluminophosphate (ALPO), and crystalline porous silicoaluminophosphate (SAPO). Zeolite is composed of a structural unit (CBU) in which multiple (several to several tens) TO4 units are connected. Therefore, it has regular channels (tubular pores) and cavities (hollow spaces).

[0020] The type of zeolite is not particularly limited and can be appropriately selected depending on the purpose, but CHA type and AEI type are preferred because they are easy to incorporate metals as described below. The type of zeolite may be one type alone or two or more types in combination. Furthermore, the zeolite to be used may be naturally occurring or appropriately synthesized.

[0021] The primary particle size of the zeolite is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.1 μm to 4.0 μm from the viewpoint of supporting the zeolite on a substrate as described below. Note that this value is a result of measurement at a diagonal of the crystal. The method for measuring the primary particle size of zeolite is not particularly limited and can be appropriately selected depending on the purpose. For example, the primary particle size of zeolite can be observed and measured using an electron microscope such as SEM (scanning electron microscope) or TEM (transmission electron microscope).

[0022] The zeolite according to the embodiment contains Cu and metals other than Cu (hereinafter also referred to as "other metals").

[0023] As the metals other than Cu, from the viewpoint of catalytic activity, Mn, Fe, Zn, La, Nd, B, and Ce are preferred, and La and Mn are more preferred. These may be used alone or in combination of two or more.

[0024] In zeolites, the ratio of the pore volume of a zeolite containing Cu and metals other than Cu to the pore volume of a zeolite not containing metals other than Cu (pore volume of a zeolite containing metals other than Cu (cm 3 / g) / pore volume of zeolite containing no metals other than Cu (cm 3 / g)) is preferably 0.85 to 0.99, and more preferably 0.87 to 0.99. When the pore volume ratio is within this range, the catalyst can achieve both NOx purification and suppression of N2O emissions.

[0025] When the ratio of the pore volume of zeolite containing Cu and metals other than Cu to the pore volume of zeolite not containing metals other than Cu (pore volume of zeolite containing metals other than Cu / pore volume of zeolite not containing metals other than Cu) is 0.85 to 0.99, the catalyst can achieve both NOx purification and suppression of NO emissions for the following reasons. In a normal SCR catalyst, the NOx reduction reaction generates N2O via the reaction intermediate NH4NO3. In contrast, in zeolites with reduced pore volume, the reaction field is narrowed (the volume of the reaction field is reduced) due to the inclusion of other metals in addition to Cu, and it is believed that N2 is generated via the reaction intermediate NH4NO2. In other words, the reduction in the volume of the reaction field suppresses the generation of NH4NO3 and generates NH4NO2, resulting in the generation of a large amount of N2.

[0026] The pore volume of a zeolite can be measured by the same method as that for measuring a normal pore volume, for example, by a multipoint method using a pore volume measuring device.

[0027] The ratio (other metals / Al) of Al to metals other than Cu (other metals) in the zeolite is preferably from 0.01 to 0.33, and more preferably from 0.01 to 0.17. The ratio of Al to other metals can be calculated, for example, by FP method measurement using XRF.

[0028] <<Other ingredients>> The other components are not particularly limited and can be appropriately selected depending on the purpose as long as they do not inhibit the activity of the catalyst. For example, zeolite that does not encapsulate metals can be mentioned. The contents of the other components are not particularly limited and can be appropriately selected depending on the purpose.

[0029] <Catalyst manufacturing method> The method for producing the catalyst is not particularly limited as long as it is possible to encapsulate a metal in zeolite, and can be appropriately selected depending on the purpose. For example, the catalyst can be produced by impregnating zeolite with a solution of copper and other metals. The concentration of the solution for impregnating the zeolite is not particularly limited and can be appropriately selected depending on the purpose.

[0030] <Other materials> The other members are not particularly limited and can be appropriately selected depending on the purpose.

[0031] <Method of manufacturing exhaust gas purification catalyst> The method for producing the exhaust gas purifying catalyst is not particularly limited and can be appropriately selected depending on the purpose. For example, the method can be performed by a step of forming a slurry of the catalyst and a step of packing the slurry.

[0032] The step of forming a slurry of the catalyst can be carried out by dispersing the zeolite-containing catalyst in water. The viscosity of the slurry is not particularly limited and can be appropriately selected depending on the purpose, but in terms of facilitating filling into the base material, it is preferably 1,700 mPa·s or less at 25° C., and more preferably about 300 mPa·s.

[0033] The step of filling the slurry is carried out by filling the substrate with the slurry obtained in the step of making the catalyst into a slurry. The amount of catalyst to be filled into the substrate is not particularly limited as long as it does not cause clogging of the substrate, and can be appropriately selected depending on the purpose. It is preferable to fill the substrate with the catalyst in an amount of 20 g / L to 250 g / L relative to the volume of the substrate. EXAMPLES

[0034] Next, the present invention will be described with reference to examples, but the scope of the present invention is not limited to these examples.

[0035] (Examples 1 to 4, Comparative Example 1) <Catalyst preparation: low SAR (silica-alumina ratio) zeolite> CHA-type zeolite (SiO2 / Al2O3=13, typical pore size: 3.8Å) was impregnated with a solution of copper nitrate (Cu(NO3)2) with Cu / Al=0.25 to obtain Cu-CHA-type zeolite. The obtained Cu-CHA-type zeolite was dried at 200℃ and then calcined at 550℃. Next, the obtained Cu-CHA type zeolite was impregnated with a mixed solution containing metal sources other than Cu in the combination shown in Table 1. The impregnated zeolite was dried at 200°C and then calcined at 550°C to obtain a CHA type zeolite encapsulating Cu and metals other than Cu.

[0036] <Preparation of slurry> 15 g of boehmite (AP-1, manufactured by JGC Catalysts and Chemicals Co., Ltd.) was added to 150 g of pure water with stirring, and 94.5 g of each of the obtained zeolites (Cu-CHA type zeolites containing metals other than Cu) was added with stirring to obtain a slurry.

[0037] <Production of exhaust gas purification catalyst> Each of the obtained slurries was used to coat a honeycomb substrate (Honeyceram 5 / 300, manufactured by NGK Insulators, Ltd.) to a concentration of 100 g / L, dried at 200°C, and then fired at 500°C. Next, in order to simulate hydrothermal degradation during use, the catalyst was treated at 650°C for 100 hours in air containing 10% moisture to obtain an exhaust gas purification catalyst.

[0038] [Table 1]

[0039] (Examples 5 to 10, Comparative Example 2) <Catalyst preparation: high SAR zeolite> CHA-type zeolite (SiO2 / Al2O3=24, typical pore size: 3.8Å) was impregnated with a solution of copper nitrate (Cu(NO3)2) with Cu / Al=0.30 to obtain Cu-CHA-type zeolite. The obtained Cu-CHA-type zeolite was dried at 200℃ and then calcined at 550℃. Next, the obtained Cu-CHA type zeolite was impregnated with a lanthanum nitrate hexahydrate (La(NO3)3·6H2O) solution in the ratio shown in Table 2. The impregnated zeolite was dried at 200°C and then calcined at 550°C to obtain a CHA type zeolite containing Cu and La.

[0040] <Preparation of slurry> 15 g of boehmite (AP-1, manufactured by JGC Catalysts and Chemicals Co., Ltd.) was added to 150 g of pure water with stirring, and 94.5 g of each of the obtained zeolites (Cu-CHA type zeolites containing La) was added thereto with stirring to obtain slurries.

[0041] <Production of exhaust gas purification catalyst> Each of the obtained slurries was used to coat a honeycomb substrate (Honeyceram 5 / 300, manufactured by NGK Insulators, Ltd.) to a concentration of 190 g / L, dried at 200°C, and then fired at 500°C. Next, in order to simulate hydrothermal degradation during use, the catalyst was treated at 650°C for 100 hours in air containing 10% moisture to obtain an exhaust gas purification catalyst.

[0042] [Table 2]

[0043] <Total pore volume measurement> The pore volumes of the catalysts (zeolites) in the exhaust gas purification catalysts of Examples 1 to 10 and Comparative Examples 1 and 2 were measured under the following conditions. From the obtained pore volume measurement results, the ratio of the pore volume of the zeolite containing metals other than Cu to the pore volume of the zeolite containing only Cu (zeolite containing no metals other than Cu) (pore volume of the zeolite containing metals other than Cu (cm 3 / g) / pore volume of zeolite containing no metals other than Cu (cm 3 The pore volume ratio (μm / g) was calculated. The results are shown in Table 3. -Conditions for total pore volume measurement- Equipment: Belsorp-miniII (manufactured by Microtrack Bel Co., Ltd.) Pretreatment conditions: 400℃, 4h (achieved vacuum pressure approx. 2Pa) Measurement conditions: multi-point method, BJH method (N2 adsorption, 77K)

[0044] <Catalyst performance evaluation> The exhaust gas purification catalysts of Examples 1 to 10 and Comparative Examples 1 and 2 were cut into a size of 25.4 mm in diameter and 25 mm in length, and placed in a catalyst evaluation device (SIGU-2000, manufactured by HORIBA Corporation, analysis by MEXA-6000FT). A mixed gas of the following composition was passed through the device, and the NO x The purification performance and the amount of N2O produced at 500°C were measured. The measurement results are shown in Table 3. -Composition of mixed gas- NO: 300 ppm NH3: 300 ppm H2O:5% / O2:10% / N2:Balance

[0045] <Observation of metal atoms in zeolite> The distribution of metals in the catalyst (zeolite) in the exhaust gas purifying catalyst of Example 9, that is, the state of metal atoms other than Cu, was observed. The zeolite to be observed was dispersed in epoxy resin, and the epoxy resin was cured. The cured product was polished and gold was evaporated to obtain a sample. By embedding the zeolite particles in resin and polishing the surface, it is possible to observe the inside of the zeolite crystals. The obtained sample was observed under the following conditions using an electron probe microanalyzer (EPMA-8050G, Shimadzu Corporation), and the positions of metal elements other than Cu in the zeolite were observed by reading element-specific signals. The observation results are shown in Figures 1A and 1B. -Measurement conditions- Acceleration voltage: 20 keV Specimen current: 30nA Measurement time: 50msec / pt

[0046] [Table 3]

[0047] Generally, NO xIn order to increase the purification rate, the amount of Cu-containing zeolite coated (supported) on the substrate can be increased. However, increasing the amount of Cu-containing zeolite coated increases the amount of NO produced as a by-product. NO x Whether or not purification and N2O emission control can be achieved at the same time depends on the NO x The amount of N2O generated when the purification rate is assumed to be the same (N2O generated (ppm) / NO x It can be evaluated by the purification rate (%). Comparative Example 1 (NO production (ppm) / NO x The purification rate (%) was 0.135 in the case of the catalyst, whereas it was 0.077 to 0.121 in the cases of Examples 1 to 4. This is because when metals other than Cu are included, the NO x If it is a purification rate, it indicates that the generation of N2O is being suppressed. In addition, the (N2O production amount (ppm) / NO x The purification rate (%) was 0.094, whereas it was 0.066 to 0.087 in Examples 5 to 10. This indicates that zeolites containing more metals other than Cu can better suppress the generation of N2O.

[0048] Figure 1A shows the results of observation of the inside of a zeolite particle without image processing. Figure 1B shows the image of Figure 1A processed to clarify the Si and La of the zeolite. As shown in Fig. 1B, La is surrounded by Si derived from the zeolite, which indicates that La is encapsulated in the zeolite.

[0049] (Examples 11 to 12, Comparative Example 3) <Catalyst preparation: low SAR (silica-alumina ratio) zeolite> CHA-type zeolite (SiO2 / Al2O3=13, typical pore size: 3.8Å) was impregnated with a solution of copper nitrate (Cu(NO3)2) with Cu / Al=0.24 or 0.25 to obtain Cu-CHA-type zeolite. The obtained Cu-CHA-type zeolite was dried at 200℃ and then calcined at 550℃. Next, the obtained Cu-CHA type zeolite was impregnated with a mixed solution containing metal sources other than Cu in the combination shown in Table 4. The impregnated zeolite was dried at 200°C and then calcined at 550°C to obtain a CHA type zeolite encapsulating Cu and metals other than Cu.

[0050] <Preparation of slurry> 15 g of boehmite (AP-1, manufactured by JGC Catalysts and Chemicals Co., Ltd.) was added to 150 g of pure water with stirring, and 94.5 g of each of the obtained zeolites (Cu-CHA type zeolites containing metals other than Cu) was added with stirring to obtain a slurry.

[0051] <Production of exhaust gas purification catalyst> Each of the obtained slurries was used to coat a honeycomb substrate (Honeyceram 5 / 300, manufactured by NGK Insulators, Ltd.) to a concentration of 100 g / L, dried at 200°C, and then fired at 500°C. Next, in order to simulate hydrothermal degradation during use, the catalyst was treated at 650°C for 100 hours in air containing 10% moisture to obtain an exhaust gas purification catalyst.

[0052] [Table 4]

[0053] <Catalyst performance evaluation> For the exhaust gas purification catalysts of Examples 11 to 12 and Comparative Example 3, the total pore volume (g / cm 3 ), NO at 200°C xThe purification rate (%) and NO production (ppm) at 500°C were measured. From these measurement results, the ratio of the pore volume of zeolite containing metals other than Cu to the pore volume of zeolite containing only Cu (zeolite containing no metals other than Cu) (the pore volume of zeolite containing metals other than Cu (cm 3 / g) / pore volume of zeolite containing no metals other than Cu (cm 3 / g) and the ratio (NO production (ppm) / NO x The purification rate (%) was calculated. The results are shown in Table 5.

[0054] [Table 5]

[0055] Comparative Example 3 (NO production (ppm) / NO x The purification rate (%) of the catalyst in Examples 11 and 12 was 0.160, whereas it was 0.090 to 0.127 in Examples 11 and 12. This is because when metals other than Cu are included, the same level of NO x If it is a purification rate, it indicates that the generation of N2O is being suppressed. From the results of Examples 1 to 12, it was found that zeolites containing metals other than Cu had similar NO x If it is a purification rate, it indicates that the generation of N2O is being suppressed.

[0056] (Example 13, Comparative Example 4) <Catalyst creation: AEI type zeolite> AEI zeolite (SiO2 / Al2O3=16, typical pore size: 3.8Å) was impregnated with a solution of copper nitrate (Cu(NO3)2) with Cu / Al=0.24 to obtain Cu-AEI zeolite. The obtained Cu-AEI zeolite was dried at 200℃ and then calcined at 550℃. Next, the obtained Cu-AEI zeolite was impregnated with a lanthanum nitrate hexahydrate (La(NO3)3·6H2O) solution in the proportions shown in Table 6. The impregnated zeolite was dried at 200°C and then calcined at 550°C to obtain AEI zeolite containing Cu and La.

[0057] <Preparation of slurry> 15 g of boehmite (AP-1, manufactured by JGC Catalysts and Chemicals) was added to 150 g of pure water with stirring, and 94.5 g of each of the obtained zeolites (Cu-AEI type zeolites containing La) was added thereto with stirring to obtain a slurry.

[0058] <Production of exhaust gas purification catalyst> Each of the obtained slurries was used to coat a honeycomb substrate (Honeyceram 5 / 300, manufactured by NGK Insulators, Ltd.) to a concentration of 100 g / L, dried at 200°C, and then fired at 500°C. Next, in order to simulate hydrothermal degradation during use, the catalyst was treated at 650°C for 100 hours in air containing 10% moisture to obtain an exhaust gas purification catalyst.

[0059] [Table 6]

[0060] <Total pore volume measurement> The pore volumes of the catalysts (zeolites) in the exhaust gas purification catalysts of Example 13 and Comparative Example 4 were measured under the following conditions. From the obtained pore volume measurement results, the ratio of the pore volume of the zeolite containing metals other than Cu to the pore volume of the zeolite containing only Cu (zeolite containing no metals other than Cu) (pore volume of the zeolite containing metals other than Cu (cm 3 / g) / pore volume of zeolite containing no metals other than Cu (cm 3 The pore volume ratio (μm / g) was calculated. The results are shown in Table 7. -Conditions for total pore volume measurement- Equipment: Belsorp-miniII (manufactured by Microtrack Bel Co., Ltd.) Pretreatment conditions: 150℃ (attained vacuum pressure of about 2 Pa) Measurement conditions: multi-point method, BJH method (N2 adsorption, 77K)

[0061] <Catalyst performance evaluation> The exhaust gas purification catalysts of Example 13 and Comparative Example 4 were cut into a size of 25.4 mm in diameter and 25 mm in length, and placed in a catalyst evaluation device (SIGU-2000, manufactured by HORIBA Corporation, analysis by MEXA-6000FT). A mixed gas of the following composition was passed through the device, and the NO x The purification rate (%) and the amount of N2O produced (ppm) at 500°C were measured. The measurement results are shown in Table 7. -Composition of mixed gas- NO: 300 ppm NH3: 300 ppm H2O:5% / O2:10% / N2:Balance

[0062] [Table 7]

[0063] Comparative Example 4 (NO production (ppm) / NO x The purification rate (%) of Example 13 was 0.100, while that of Example 11 was 0.118. This is because when metals other than Cu are included, the same level of NO x If it is a purification rate, it indicates that the generation of N2O is being suppressed.

[0064] From the above, it is considered that the exhaust gas purification catalyst using zeolite containing Cu and metals other than Cu has a high NO x It became clear that it was possible to achieve both purification and the reduction of N2O emissions.

Claims

1. A catalyst for purifying exhaust gas, comprising a substrate and a catalyst supported on a surface of the substrate, 1. A catalyst for purifying exhaust gas, comprising a zeolite containing Cu and a metal other than Cu.

2. In the zeolite, the ratio of the pore volume of the zeolite containing Cu and the metal other than Cu to the pore volume of the zeolite not containing the metal other than Cu (pore volume of the zeolite containing the metal other than Cu (cm 3 / g) / Pore volume of zeolite containing no metals other than Cu (cm 3 2. The exhaust gas purifying catalyst according to claim 1, wherein the molar ratio (R / g) is 0.85 to 0.

99.

3. In the zeolite, the ratio of the pore volume of the zeolite containing Cu and the metal other than Cu to the pore volume of the zeolite not containing the metal other than Cu (pore volume of the zeolite containing the metal other than Cu (cm 3 / g) / Pore volume of zeolite containing no metals other than Cu (cm 3 3. The exhaust gas purifying catalyst according to claim 1, wherein the molar ratio (R / g) is 0.87 to 0.

99.

4. 3. The exhaust gas purifying catalyst according to claim 1, wherein the metal other than Cu is at least one selected from the group consisting of Mn, Fe, Zn, La, Nd, B and Ce.

5. 3. The exhaust gas purifying catalyst according to claim 1, wherein the metal other than Cu is at least one selected from the group consisting of La and Mn.

6. 3. The exhaust gas purifying catalyst according to claim 1, wherein the ratio of Al in the zeolite to the metals other than Cu (metals other than Cu / Al) in the catalyst is 0.01 to 0.33.

Citation Information

Patent Citations

  • Exhaust gas purification catalyst device

    JP2023079713A